Hidden Curriculum Pendidikan Agama Islam dan Urgensinya di Pesantren: Studi di Madrasah Diniyyah Haji Ya’qub Lirboyo Kediri - Harun, Muhammad (Indonesian Proceedings and Annual Conference of Islamic Education (IPACIE), 2022)
One of the keys to educational institutions is the curriculum. The better and superior and tested the quality of learning delivered by teachers or lecturers will also be. Of course, this curriculum cannot run optimally without the support of adequate resources. In this case, the hidden curriculum is one solution to increasing the quality and character of students. The role of the teacher accompanies application and implementation support, so it is hoped that superior education can be achieved. On that basis, the author will try to focus his research on uncovering the hidden curriculum of Islamic education and its urgency at Madrasah Diniyyah Haji Ya'qub Lirboyo Kediri. How are the situations and conditions in the madrasa and its implementation so that students can become individuals with character, think critically, independently, competitively, have a social spirit, and become creative and innovative advanced individuals? In this case, of course the role of the teacher will also be discussed, so that the writer knows; the extent to which the usatdz in Madrasah Diniyyah Haji Ya'qub play a role in educating and printing students according to expectations. Likewise, the involvement of Kyai and his family in guiding and motivating, and suggesting students in achieving and producing quality education.